2020
DOI: 10.3389/fcvm.2020.00063
|View full text |Cite
|
Sign up to set email alerts
|

Which Biological Properties of Heart Valves Are Relevant to Tissue Engineering?

Abstract: Over the last 20 years, the designs of tissue engineered heart valves have evolved considerably. An initial focus on replicating the mechanical and structural features of semilunar valves has expanded to endeavors to mimic the biological behavior of heart valve cells as well. Studies on the biology of heart valves have shown that the function and durability of native valves is underpinned by complex interactions between the valve cells, the extracellular matrix, and the mechanical environment in which heart va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 93 publications
0
21
0
Order By: Relevance
“…The monocusp leaflet, however, typically becomes immobile independent of the prosthetic material (e.g., 0.1 mm ePTFE or autologous pericardium is used) on long-term [ 85 ]. There are currently various tissue-engineering attempts to develop viable implants focusing on rheological properties, structural and viability aspects [ 86 , 87 , 88 , 89 ].…”
Section: Biomaterials Clinically Utilized In Congenital Cardiac Sumentioning
confidence: 99%
“…The monocusp leaflet, however, typically becomes immobile independent of the prosthetic material (e.g., 0.1 mm ePTFE or autologous pericardium is used) on long-term [ 85 ]. There are currently various tissue-engineering attempts to develop viable implants focusing on rheological properties, structural and viability aspects [ 86 , 87 , 88 , 89 ].…”
Section: Biomaterials Clinically Utilized In Congenital Cardiac Sumentioning
confidence: 99%
“…Unfortunately, the preliminary results of these trials have demonstrated some significant valve-related complications that have prevented their widespread use, most notably leaflet retraction which leads to regurgitation. Currently available TEHV can broadly be separated into two categories, based on the scaffold used to create the TEHV [ 153 ]. Synthetic scaffolds are typically fabricated from man-made synthetic polymers including a variety of biomaterials such as polyglycolic acid, polycaprolactone, and 4-hydroxybuterate.…”
Section: Ecm and Therapeuticsmentioning
confidence: 99%
“…The integrity of the entire matrix during the lifetime of the valve relied on matrix proteins and remodeling enzymes provided by the valve interstitial cells. And the formation of a continuous endothelium that mediated hemostasis and inflammation was promoted by the adhesion of valve endothelial cells to the basement membrane laminins 49 . Therefore, the TEHV scaffold should have a suitable degradation rate to support the cells to produce enough extracellular matrix and maintain the normal physiological function of the valve before that.…”
Section: Biodegradable Synthetic Polymer‐based Scaffoldmentioning
confidence: 99%
“…First of all, the blood‐contacting surfaces of the TEHV scaffold must be smooth enough with a low friction coefficient to prevent thrombosis, coagulation, or calcification 53 . Moreover, we can adopt some strategies such as the seeding of endothelial cells onto the surface of scaffolds, the attraction of circulating endothelial progenitor cells onto implanted valves, incorporation of anticalcification agents into the scaffold material and so on 49 …”
Section: Biodegradable Synthetic Polymer‐based Scaffoldmentioning
confidence: 99%